(3eG JOYh Edjg GdMGLI ef Sff GHf eGLIs - (3TeS GdOjf CHi GdQVG eMeO Hf MSf GdRHjQis; (3eMeO Hf jRjO GdQHYj GdbRhjfj, CHh YHO Gddg, GHf eGLI,J (B273 (3g` s
(3ChdgG (B:s
(3jHOC HCHhGH EbGeI GdUdhGJ s
(3BNQgG (B:s
(3jfJgi HHGH hbJ UdGI GdYjOjf s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B115s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B2424) s
Keywords: (3GdMOjK h GdeUWdMs